2023
DOI: 10.1111/pace.14700
|View full text |Cite
|
Sign up to set email alerts
|

Left bundle branch pacing versus biventricular pacing for cardiac resynchronization therapy: A systematic review and meta‐analysis

Abstract: Introduction: Cardiac resynchronization therapy (CRT) reduces heart failure (HF) hospitalization and all-cause mortality in HF patients with left bundle branch block (LBBB).Biventricular pacing (BVP) is the gold standard for achieving CRT, but about 30%-40% of patients do not respond to BVP-CRT. Recent studies showed that left bundle branch pacing (LBBP) provided remarkable results in CRT. Therefore, we conducted a meta-analysis aiming to compare LBBP-CRT versus BVP-CRT in HF patients. Methods:We systematicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
3
4
0
Order By: Relevance
“…Compared to BVP, the LBBP group demonstrated significantly lower capture thresholds at baseline and at 12 months follow-up, which is in line with previous results [ 20 , 26 ]. Lower capture thresholds may increase battery life time.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Compared to BVP, the LBBP group demonstrated significantly lower capture thresholds at baseline and at 12 months follow-up, which is in line with previous results [ 20 , 26 ]. Lower capture thresholds may increase battery life time.…”
Section: Discussionsupporting
confidence: 92%
“…As a consequence, greater resynchronization with LBBP translated into a 6 % greater improvement in LVEF as compared to BVP. Recently, in CRT candidates with LBBB Parlavecchio et al [ 20 ] demonstrated that the increase in LVEF with LBBP was 5.8 % higher as compared to conventional BVP, which is comparable to our data. The pronounced decrease in LVESV in LBBP compared with BVP (−53 ml versus −13 ml, respectively) corroborates significant reverse remodelling upon LBBP.…”
Section: Discussionsupporting
confidence: 91%
“…These findings align with a recent meta-analysis that also demonstrated a favorable effect of LBBAP over BiVP in reducing HF hospitalizations. 20 Similarly, our meta-analysis demonstrated improved survival in patients undergoing LBBAP as compared with BiVP. Our results are in contrast with the 2 of the included studies that did not find any mortality benefit with LBBAP use.…”
Section: Discussionsupporting
confidence: 55%
“…This meta-analysis is an updated analysis that includes 12 studies (3004 patients) and provides more robust evidence than previous meta-analyses that included fewer studies. 18 , 19 , 20 Notably, this is the first meta-analysis to report a mortality benefit with LBBAP over BiVP in patients with systolic HF.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, the rate of echocardiographic response (defined as an absolute increase in LVEF by ≥5% between baseline and follow-up) and super-response (defined as an absolute increase in LVEF ≥20% or LVEF ≥50%) is significantly higher in patients undergoing LBBAP compared with BiVp (88.5 versus 72.5%; p=0.002; and 60.8 versus 36.5%, p<0.001, respectively). [ 45 ]…”
Section: Evidence Supporting the Use Of Left Bundle Branch Area Pacin...mentioning
confidence: 99%